Aulacoseira capitalina sp. nov. (Bacillariophyta) from the Middle Miocene sediments of the Barguzin Valley, Baikal Rift Zone (Russia) - Lybov’ А. Titova; Abdulmonem I. Hassan; Marina V. Usoltseva (Acta Biologica Sibirica, 2022)
Using light and scanning electron microscopy, a new species Aulacoseira capitalina Titova et Usoltseva from the Middle Miocene deposits of the Barguzin Valley is described. It is shown that the new species is similar to other elliptical species in terms of elliptical valve face profile, diameter, deep ringleist, but differs in the shape of separating spines, the absence of ridge structure and the shape of rimoportulae. The finding of A. capitalina in the Middle Miocene deposits of the Barguzin Valley expands the range of distribution of elliptical species.